UJI BAHAN PLAT DRUM PADA TEMPERATUR 100C, 200C, 300C, 400C, 500C DENGAN UJI KEKERASAN - Muh Anhar (Universitas PGRI Semarang, 2019)
The hardness of a material in general, states against deformation and for metals with these properties is a measure of its resistance to plastic deformation or permanent deformation. if that states violence as a measure of indentation and there is also a definition of violence as a measure of convenience and a special quantity that shows something about the strength and heat treatment of a metal.The hardness value of the material changes when given heat treatment at a temperature of 100 C, 200C, 300C, 400C, 500C. Color changes in materials when heated at temperatures of 100 C, 200C, 300C, 400C, 500C. indicates a change in metal elements that occur in the material. The results of the hardness of the heat treated material increased harder than the initial material without heat treatment, which was produced after the hardness test was 18.17%.